Exploration of Biology Learning Experiences Among Students of SMAN 3 Singaraja: A Review of Offline and Online Learning - I Putu Oktap Indrawan; Ilma Wiryanti; Kadek Sudarsini (UHN IGB Sugriwa Denpasar, 2023)
This study aims to explore the learning experiences of biology students, particularly within the realms of face-to-face and online learning, and to identify solutions for enhancing the quality of education. The research methodology employed is the Convergent Mixed Methods Design. The participants in the study encompassed 43 twelfth-grade students specializing in the natural sciences (IPA) and three biology teachers. Data collection was conducted through questionnaires, interviews, and observations, followed by a comprehensive analysis employing both quantitative and qualitative descriptive techniques. The research findings reveal that the primary challenges faced by students in the realm of biology education include difficulties in recalling scientific terminology, inadequate preparation prior to lessons, limited engagement with everyday biological issues, struggles in time management for studying, a lack of focus during learning, and difficulties in comprehending biological concepts. Over half of the students exhibit a preference for face-to-face learning, though online learning and hybrid modes are also popular. Among the Learning Management Systems (LMS) in use, Google Classroom stands out as the most frequently employed. The principal sources of internet access for the students include home Wi-Fi, tethering from the devices of parents, siblings, or friends, and internet cafes. While internet connectivity at school is generally available, the issue of unstable signals persists. The research outcomes carry significant implications for the development of more effective strategies in biology education, such as interactive approaches, the integration of real-world contexts, and the augmentation of digital infrastructure. Additionally, external factors and social considerations necessitate careful consideration in the development of comprehensive teaching strategies.